Penggunaan Sistem Informasi dan Kinerja Karyawan - Manacika, Dewa Ngakan Gede Galang; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 33 No 6 (2023), 2023)
The study of various factors that influence the use of information systems on the performance of village credit institution (LPD) employees is the focus of this research. This research was chosen to be conducted in Gianyar Regency. The population in the study included all LPD employees in Gianyar who were registered with the Gianyar Village Credit Empowerment Institute (LPLPD) and obtained a sample size that met the criteria of 126 respondents. Multiple linear regression analysis is the chosen analytical technique. The findings obtained based on the analysis of respondents' answers show that Social influence significantly influences perceived usefulness, facilitating and Computer self-efficacy has a significant effect on perceived ease of use, Perceived usefulness and Perceived ease of use have a significant positive effect on the attitude of using information systems, and Attitudes of using information systems have a significant effect on employee performance. Keywords: Social Influence; Computer Self Efficacy; Perceived Usefulness; Perceived Ease of Use